Experimental evaluation of parrot-inspired robot and adapted model-rival method for teaching children with autism - Bharatharaj, Jaishankar; Loulin Huang; Al-Jumaily, Ahmed M.; Krageloh, Christian; Elara, Mohan Rajesh (2016 14th International Conference on Control, Automation, Robotics and Vision (ICARCV), 2016)
The use of biologically inspired robots in therapeutic settings could offer new possibilities for improving learning and social interaction abilities of children with autism. This paper introduces a novel teaching method, Adapted Model-Rival Method, together with a parrot-inspired robot (KiliRo) to help children with autism in learning and social interaction. The proposed indirect teaching method and the parrot-like robot morphology were tested with 9 children identified with autism. The test was conducted for 5 consecutive days for the same participants at the same place. In this study, the emotions of participating children during the experiment were analyzed using an automated emotion recognition and classification system, Oxford emotion API through facial images. Totally, 580 pictures were taken to obtain 2360 individual facial emotion values for evaluation. The results show that the happiness of subjects improved from day 1 through day 5 of the study through interacting with the robot. It is also reported that the participating children were attracted to the robot when it was exhibiting its learning abilities. Our study also indicates that the children with autism are not afraid of parrot-like robots and are happy to interact with it.